Comparison of outcomes of thrombocytopenic and non-thrombocytopenic culture proven neonatal sepsis - Patel, Saumil M.; Patel, Kinjal; Patel, Karan; Thaddanee, Rekha (International Journal of Contemporary Pediatrics, 2021)
Background: Due to high incidence of sepsis as a main cause of neonatal mortality, early detection and proper treatment are important in reducing neonatal mortality. Thrombocytopenia is a common hematological problem encountered during neonatal period, particularly in neonatal sepsis. This study was done to know the incidence of thrombocytopenia in neonatal sepsis and to compare clinical outcome in patients with thrombocytopenic and non-thrombocytopenic neonatal sepsis. Methods: This was a prospective study carried out at neonatal intensive care unit of a tertiary care teaching hospital of western Gujarat, India, from October 2018 to August 2020. 2739 neonates were admitted with probable sepsis during study period. 299 neonates with positive blood cultures were recruited for the study. They were divided into two groups; group-1 had patients with thrombocytopenia, while group-2 included patients without thrombocytopenia. Severity of thrombocytopenia was assessed in group-1. Micro-organisms isolated and outcome of sepsis were compared in both the groups. Results: There were 208 neonates in group-1 (thrombocytopenic) and 91 in group-2 (non-thrombocytopenic). There was no significant difference in demographic profiles of neonates in both groups. Klebsiella pneumonia was the most common organism isolated from 79 patients of group-1 and 19 patients of group-2 (p=0.033). Coagulase negative Staphylococci and Candida were the second and third most common micro-organisms isolated from 30.2% and 15.1% of blood cultures respectively. In group-1, 85 (40.8%), 72 (34.6%) and 51 (24.5%) neonates had severe, moderate and mild thrombocytopenia respectively. Klebsiella pneumoniae (45.9%) was the commonest organism isolated in severe thrombocytopenic neonates, followed by Candia (22.4%) and Enterococcus (14.1%). Conclusions: Thrombocytopenia is a specific marker of neonatal sepsis. The platelet count is a simple test that facilitates diagnostic orientation and the establishment of an early empirical treatment. Klebsiella pneumoniae was the commonest organism isolated in severe thrombocytopenic neonates.